DETEKSI PERILAKU HERDING PADA PASAR SAHAM INDONESIA & SINGAPURA TAHUN 2011 – 2015 - Ramadhan, Taofan; Mahfud, M. Kholiq (Faculty of Economics and Business Diponegoro University, 2016)
Herding behavior is one of the investor's irrational behavior that can destabilize the stock market. When herding happened, investors tend not to use the analysis in making investment decisions but follow the market consensus or imitate a decision of other investors.This study discusses whether herding behavior occurs in emerging market specifically Indonesia Stock Market and also developed market specifically Singapore Stock Market. By looking at the relationship between return market portfolio and Cross Sectional Absolute Deviation (CSAD), then herding behavior in a market can be identified. Herding detection performed on different market conditions, so this study using quantile regression analysis.The result of this study shows that there is no indication of herding behavior in both stock market, which means that investors tend to behave rationally in making investment decisions.